Urban Transformation and Property Value Variation. The Role of HS Stations - Gargiulo, Carmela; De Ciutiis, Fiorella (TeMA - Journal of Land Use, Mobility and Environment, 2010)
The article aims reading and interpreting the positive externalities, especially in terms of urban redevelopment, connected to the building of node/station of the High Speed railway network. The measure of the variations of the real estate values, carried out through the analysis of numerous European andItalian experiences, is considered as a synthetic indicator of urban quality consequent to the strengthening or establishment of a new High Speed station. The identification of relationships between High Speed station, residential property values and typologies of cities (role and urban specialization) and urban context in which the station are located is one of the conclusions of this work. In accord with the aim, this paper is organized in three principal parts. The first part identifies the relation between urban transformations, urban quality and property values and provides a scientific frame of the studies on the relationships between accessibility increase and property values. Indeed, the results of many studies and reports reveal that the reduction in generalized cost of transport and the increase of accessibility related to the implementation of new infrastructure such as a railway station, in some cases have impacted significantly on increasing demand for space in the surrounding areas and, accordingly, on property values. The second part proposes the reading of some experiences of building of High Speed stations in some European and Italian cities, with a focus on the case of Roma-Napoli High Speed line. The choice of cases was made using criteria that seem to give a guarantee of representativeness to the variety and multiplicity of experiences. In particular, the criteria used are: geographic location of railway line (selecting cases with different geographical locations); city-node size (choosing different types of cities for size and population), functional role of the city-node, timing for the completion of railway line (fully in operation, partly in operation or not yet in operation). Besides, the description of each case is divided into: summary description of the characteristics of the HS railway line; description of the main features of cities that represent the nodes of the selected routes; identify the characteristics of the surrounding context of the railway station;measurement of the change in property values in the surrounding context of the railway station due to HS link. The third part provides a comparative outline of the effects of High Speed stations on property values and the urban typologies and characteristics that influence this relation. The first result of this article is a comparative framework between all study cases. In conclusion, the comparative reading shows that the effect from opening of the High Speed railway stations on property values is valuable in cases where it contributes significantly to raising the socio-economic and the quality conditions of spaces.